Textbook of Dermatologic Ultrasound - Wortsman, Ximena; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides a pedagogical guide to dermatologic ultrasound. As in any imaging field, dermatologic ultrasound is dynamic, and the area expands with the release of new technology. This textbook is a mix of the essential knowledge necessary to start and a detailed update to the dermatologic ultrasound field. This book is divided into three sections: The Requisites, Ultrasound Features of Common Dermatologic Conditions, and Practicalities. The first section details the basic information needed in dermatologic ultrasound, including technical recommendations and dermatologic concepts. The second covers major dermatologic conditions and their ultrasound presentation, including benign and malignant skin tumors, pediatric conditions, nail entities, inflammatory conditions, infections and infestations, and aesthetics. The final section covers tips for reporting and interventional dermatologic ultrasound procedures.Chapters present substantial clinical, ultrasonographic, and histologic correlation, including algorithms to help discriminate different conditions. The book additionally includes 150 self-assessment questions (CME), multiple key points, a plethora of state-of-the-art images with probes that go from 18 to 70 MHz, and ultrasound videos. This is a must guide for physicians, residents, and students in radiology, dermatology, plastic surgery, and any professional who wants to brush up on the dermatologic ultrasound field.
SECTION I-The Requisites -- Technical Recommendations, Settings, and Protocols -- Dermatologic Concepts and Terminology -- Ultrasound Concepts and Terminology -- Comprehensive Anatomy of the Normal Skin, Nail, Hair and Adjacent Structures -- Relevant Topographic Anatomy, Anatomical Variants and Risk Zones -- SECTION II-Ultrasound Features of Common Dermatologic Conditions -- Ultrasound of Congenital Cutaneous Conditions -- Ultrasound of Non-Vascular Tumors and Pseudotumors -- Ultrasound of Skin Cancer -- Ultrasound of Vascular Anomalies and Tumors -- Ultrasound of Dermatologic Inflammatory Conditions -- Ultrasound of Common Infections and Infestations -- Ultrasound of Nail Conditions -- Ultrasound in Aesthetics -- Ultrasound in Pediatric Dermatology -- SECTION III- Practicalities -- Tips for Reporting the Examinations -- Tips for Ultrasonographic Marking of the Lesions.
Keywords: Radiology; Dermatology; Surgery, Plastic; Radiology; Dermatology; Plastic Surgery; Skin Diseases -- diagnostic imaging; Ultrasonography; Handbook